2019
DOI: 10.1002/jmv.25454
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy of sofosbuvir plus ribavirin in Chinese patients with genotype 3a or 3b HCV infection

Abstract: Background and Aim: Genotype 3b hepatitis C virus (HCV) infection represents approximately 50% of patients with genotype 3 in China. We compared the efficacy of sofosbuvir (SOF) plus ribavirin (RBV) in Chinese patients with genotype 3a and 3b HCV. Methods: The analyzed data are from a phase 3, open-label study of SOF plus RBV for 24 weeks conducted in China. The primary endpoint for the trial was sustained virologic response at 12 weeks after the end of therapy (SVR12).Results: Of 126 patients included in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…Most GT3 patients in our study were treated with SOF + RBV or SOF + DCV + RBV for 24 weeks. Our results are consistent with the findings of a phase 3 clinical trial in which SOF + RBV was administered during 24 weeks to treat Chinese patients with GT3 HCV infection (Huang et al, 2019). The investigators also noted that the presence of cirrhosis lowered SVR rates and the patient who relapsed had genotype 3b infection and cirrhosis.…”
Section: A B Csupporting
confidence: 90%
“…Most GT3 patients in our study were treated with SOF + RBV or SOF + DCV + RBV for 24 weeks. Our results are consistent with the findings of a phase 3 clinical trial in which SOF + RBV was administered during 24 weeks to treat Chinese patients with GT3 HCV infection (Huang et al, 2019). The investigators also noted that the presence of cirrhosis lowered SVR rates and the patient who relapsed had genotype 3b infection and cirrhosis.…”
Section: A B Csupporting
confidence: 90%
“…In Chinese phase 3 clinical trials, the SVR12 rates in GT3a-infected patients receiving 12 weeks of SOF/VEL and 24 weeks of SOF+RBV were 91% (20/22) (89% [17/19] and 100% [3/3] in patients without and with compensated cirrhosis, respectively) and 100% (58/58), respectively, 45 , 46 similar to those reported among Western GT3-infected patients. 22 , 39 Since the prevalence of Y93H (the predominant NS5A RAS affecting the efficacy of SOF/VEL in GT3a-infected patients) is lower in China, 6 , 23 it is reasonable to anticipate SOF/VEL to have similar or better efficacy in Chinese GT3a-infected patients.…”
Section: Clinical Data For Daas In Gt3-infected Patientssupporting
confidence: 65%
“…In the phase 3 trial of SOF/VEL, the overall SVR12 of SOF/VEL was 98% (40/41) in genotype 3a patients, but it was 75% (30/40) in genotype 3b patients [23]. A recent study compared the efficacy of SOF plus RBV for 24 weeks in Chinese patients with HCV genotype 3a and 3b and showed that the SVR12 rate in patients with genotype 3b [91% (62/68)] was lower than that in patients with genotype 3a [100% (58/58)] infection [28]. It is suggested that the efficacy of SOF-based regimens may differ between genotype 3a and 3b patients although the present study did not include genotype 3b patients and additional study is needed to clarify this issue.…”
Section: Discussionmentioning
confidence: 99%